Synthesis of Colloidal Ruthenium Nanocatalyst by Chemical Reduction Method - R. G. Patharkar; S. U. Nandanwar; M. Chakraborty (Journal of Chemistry)
Colloidal ruthenium nanoparticles were prepared by chemical reduction of ruthenium trichloride (RuCl3) using sodium borohydrate (NaBH4) as reducing agent and sodium dodecyl sulfate (SDS) as a stabilizer. Size and size distribution of synthesized colloidal Ru nanoparticles were studied by varying different parameters such as molar ratio (MR) of SDS/RuCl3, NaBH4/RuCl3, effects of different stabilizers, and reducing agents. Prepared nanoparticles were characterized by transmission electron microscope (TEM) and dynamic light scattering (DLS). Stability of colloidal nanoparticles was detected by Turbiscan. Stable Ru nanoparticles were dispersed on γ-Al2O3 to prepare Ru/γ-Al2O3 catalyst. This catalyst was characterized by X-ray Diffraction (XRD) and transmission electron microscope (TEM).